2015
DOI: 10.1111/jbg.12187
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a calving QTL on Bos taurus autosome 18 in Holstein cattle

Abstract: Decreased calving performance not only directly impacts the economic efficiency of dairy cattle farming but also influences public concern for animal welfare. Previous studies have revealed a QTL on Bos taurus autosome (BTA) 18 that has a large effect on calving traits in Holstein cattle. In this study, fine mapping of this QTL was performed using imputed high-density SNP chip (HD) genotypes followed by imputed next-generation sequencing (NGS) variants. BTA18 was scanned for seven direct calving traits in 6113… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Alternatively, animals suffering from mastitis may have low immunity to other infections (Sordillo, 2005), which would increase their chances of being culled. The QTL on chromosome 18 overlaps with calf size and calving difficulty QTL in the same populations (Mao et al, 2015). A large size calf can cause damage of the birth canal of a cow during calving, which may lead to a higher risk of culling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, animals suffering from mastitis may have low immunity to other infections (Sordillo, 2005), which would increase their chances of being culled. The QTL on chromosome 18 overlaps with calf size and calving difficulty QTL in the same populations (Mao et al, 2015). A large size calf can cause damage of the birth canal of a cow during calving, which may lead to a higher risk of culling.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP on RDC-CHR6-88MB with highest significance explained 1.4% of the total variance in the deregressed proofs of longevity (Table 1). Mao et al (2015) reported a major QTL affecting birth index in this HOL population, with the most associated SNP at 57,548,213 bp that explained 4.16% of the total genetic variance for birth index. It is possible that this QTL increases calving difficulties by increasing calf size at birth.…”
Section: Within-breed Association Analysesmentioning
confidence: 98%
See 1 more Smart Citation
“…Maps allow identification of loci determining specific phenotypes, such as genomic regions underlying economically important traits (Mao et al 2015; Royaert et al 2016), or genetic basis of adaptive ecological traits, such as migration (Hale et al 2013) or industrial melanism (van’t Hof et al 2016). In comparative genomics, linkage maps are indispensable to investigate the conservation of chromosomal segments at various evolutionary time scales (Postlethwait et al 2000; Hollenbeck et al 2015).…”
mentioning
confidence: 99%
“…SNPs have been widely used in a variety of genetic studies and applications, such as mapping of QTL (Kim et al ; Höglund et al ; Mao et al ), GWASs (Chan et al ; Macciotta et al ; Schweer et al ) and genomic selection (Wiggans et al ; Okut et al ; Boerner et al ; Lopes et al ) in farm animals. Over the years, ad‐hoc procedures have been used for designing SNP chips.…”
mentioning
confidence: 99%